2021
DOI: 10.3390/v13050933
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Inbred Chicken Lines Reveals Infectious Bursal Disease Severity Is Associated with Greater Bursal Inflammation In Vivo and More Rapid Induction of Pro-Inflammatory Responses in Primary Bursal Cells Stimulated Ex Vivo

Abstract: In order to better understand differences in the outcome of infectious bursal disease virus (IBDV) infection, we inoculated a very virulent (vv) strain into White Leghorn chickens of inbred line W that was previously reported to experience over 24% flock mortality, and three inbred lines (15I, C.B4 and 0) that were previously reported to display no mortality. Within each experimental group, some individuals experienced more severe disease than others but line 15I birds experienced milder disease based on avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, transcriptomic analysis revealed that more severe disease in line W chicken was associated with significant up-regulation of pathways involved in inflammation, cytoskeletal regulation by Rho GTPases, and Wnt signaling in the bursa, etc. [ 13 ] And another research focused on cecum of 1-day-old chickens infected with SE by RNA-seq, and 104 differentially expressed genes were identified, included IL-22 , IL-1β , etc. inflammation-related genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transcriptomic analysis revealed that more severe disease in line W chicken was associated with significant up-regulation of pathways involved in inflammation, cytoskeletal regulation by Rho GTPases, and Wnt signaling in the bursa, etc. [ 13 ] And another research focused on cecum of 1-day-old chickens infected with SE by RNA-seq, and 104 differentially expressed genes were identified, included IL-22 , IL-1β , etc. inflammation-related genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, IBD is still one of the most economically important immunosuppressive disease affecting young chickens aged 3–6 weeks old. Previous investigations into the virus’s pathogenesis have predominantly focused on host-pathogen interaction using Omics studies, both in vitro and in vivo , primarily involving host cell type such as fibroblast, DF-1 cells and bursal cells ( 16 , 19 21 , 47 , 48 ). However, the thymus, serving as the central immune organ responsible for T cell maturation and differentiation, has been confirmed as an important target tissue in IBDV pathogenesis ( 6 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings collectively underscore the important role of thymic pathogenicity in contributing to the immunosuppression/pathology caused by IBDV in the infected chickens. While the BF has been confirmed to be one of the most important target organ for IBDV, numerous researches have focused on deciphering the pathogenicity mechanisms of IBDV by examining changes in the BF or in vitro cultured immune cells (15)(16)(17)(18)(19)(20)(21)(22)(23). However, there are no reports on the molecular pathogenesis of IBDV in the thymus currently.…”
Section: Introductionmentioning
confidence: 99%
“…A broad search of the literature was completed in order to classify lines as either susceptible or resistant to each virus, as much as was possible. Studies of IBV (Bumstead et al, 1989; Cook et al, 1990; Nakamura et al, 1991; Otsuki et al, 1990), IBDV (Asfor et al, 2021; Bumstead et al, 1993; Farhanah et al, 2018; Smith et al, 2015b), MDV (Burgess et al, 2001; Cole, 1968; Mohd Isa et al, 2020) and AIV (Ruiz‐Hernandez et al, 2016) infections were referenced.…”
Section: Methodsmentioning
confidence: 99%